The Cambridge Big Book of Nursery Rhymes (big book) - Lewis, Anthony (Cambridge University Press Australia, 1996)
The Cambridge Big Book of Nursery Rhymes aims both to familiarise children with traditional rhyme and develop their understanding of rhyme.